Effect of ASTRA-BEN 20® on Broiler Chicks Exposed to Aflatoxin B1 or T2 Toxin - Fairchild, A.S.; Croom, J.; Grimes, J.L.; Hagler, Jr., W.M. (International Journal of Poultry Science, 2008)
The objectives of this study were: 1) to examine effects of a dietary sodium bentonite, ASTRA-BEN-20® (AB20) [Prince Agri Products, Inc., Quincy, Ill.], on in vitro binding of T2 toxin and aflatoxin B1 (AFB1); and 2) to examine the effects of AB20 in broiler chicks fed 6 ppm dietary T2 toxin (T2) or 4 ppm aflatoxin B1 (AFB1) to 21 d. Day-old male broiler chicks were randomly placed in batteries and assigned to one of nine dietary treatments (7 replicates of 5 chicks): control (C); 1% AB20; 2% AB20; T2; T2+ 1% AB20; T2+2% AB20; AFB1; AFB1+1% AB20; and AFB1+2% AB20. Individual BW, feed consumption by pen, period and cumulative feed conversions (PFC and CFC, respectively), and BW gains (BWG) were determined weekly. Liver weight (LW), relative liver weight (RLW), and liver lipid (%, PLL) were determined at d21 for AFB1 chicks. Oral lesions were scored on d21 for T2 chicks. One and 2% AB20 reduced BW during wk 1 and 2 compared to controls. AFB1 reduced BW during wk 2 and 3 and increased PLL at d21. Both 1 and 2% AB20 returned BW, BWG, and PLL to control levels. T2 reduced BW and BWG at wk 1, 2, and 3. T2 + 1% AB20 and T2 + 2% AB20 improved BW at wk 1 and 2 and BWG at wk 1 while T2 + 1% AB20 improved BW at wk 3 when compared to T2. T2 + 2% AB20 also decreased oral lesion severity compared to T2 at d21. PFC and CFC were increased by T2 and T2 + 1% AB20. CFC tended to improve when chicks were fed T2 + 2% AB20 (P<0.06). AB20 protected broiler chicks from dietary AFB1 and provided some protection against dietary T2.